2008
DOI: 10.1590/s0100-40422008000700013
|View full text |Cite
|
Sign up to set email alerts
|

Atividade biológica do lapachol e de alguns derivados sobre o desenvolvimento fúngico e em germinação de sementes

Abstract: . The natural quinones lapachol, α-lapachone and β-lapachone, and the synthetic derivative β-lapachone-3-sulfonic-acid were assayed for inhibition of fungal growth (Fusarium oxysporum) and germination of lettuce seeds (Lactuca sativa L.). β-Lapachone has the strongest activity as a germination inhibitor and lapachol shows no effect. β-Lapachone, followed by lapachol, are the most active in reducing fungal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…On the other hand, others authors showed the action of essential oils and natural products on microorganisms of agricultural significance [19] [20] and on the seed germination [21] [22]. In this context, the search for new natural products becomes a valuable alternative to the conventional use of pesticides, used against cultivated plants diseases.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, others authors showed the action of essential oils and natural products on microorganisms of agricultural significance [19] [20] and on the seed germination [21] [22]. In this context, the search for new natural products becomes a valuable alternative to the conventional use of pesticides, used against cultivated plants diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the antifungal activity in studies performed by Souza et al . (), lapachol displayed 92·8% growth inhibition of Fusarium oxysporum .…”
Section: Resultsmentioning
confidence: 93%
“…Lapachol is considered the most versatile naphtoquinone among many other biological activities (Hussain et al 2007). Regarding the antifungal activity in studies performed by Souza et al (2008), lapachol displayed 92Á8% growth inhibition of Fusarium oxysporum.…”
Section: Identification Of Compounds By Gc-msmentioning
confidence: 99%
“…Os derivados 2, 3, 4 e 6 foram preparados segundo técnicas descritas por Souza e colaboradores (2008) empregando o lapachol 1, previamente extraído e purificado, como material de partida. 12…”
Section: Síntese Dos Compostos De Interesseunclassified